2021
DOI: 10.47836/pjssh.29.s3.10
|View full text |Cite
|
Sign up to set email alerts
|

In-service Teachers’ Familiarisation of the CEFR-aligned School-based Assessment in the Malaysian Secondary ESL Classroom

Abstract: The main purpose of this study is to investigate in-service teachers’ familiarization of the CEFR-aligned school-based assessment (SBA) in the Malaysian secondary ESL classroom. It also intends to explore teachers’ knowledge, understanding, and perceptions of the CEFR-aligned SBA. The study also examined the implementation of the SBA and the challenges that TESL teachers faced embracing the CEFR-aligned SBA in their ESL classroom. An exploratory mixed-method research design was employed. Data were collected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…This implied that teachers' positive attitude and acceptance to CEFR implementation improved their motivation level, thus resulted in positive upshots of the implementation. The findings from a study by Singh et al, (2021) communicated that local TESL in-service teachers have rather a good level of familiarization with CEFR-aligned SBA, and a moderate level of awareness and comprehension of the CEFR-aligned SBA. Reviews of past documents conducted by Zaki and Darmi (2021) showed that the implementation CEFR in classroom assessments gives several benefits to the teachers such as to track learners' learning progress, and identify learners' strengths and weaknesses in learning, so as they can plan and modify teaching methods, and take immediate follow-up actions.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…This implied that teachers' positive attitude and acceptance to CEFR implementation improved their motivation level, thus resulted in positive upshots of the implementation. The findings from a study by Singh et al, (2021) communicated that local TESL in-service teachers have rather a good level of familiarization with CEFR-aligned SBA, and a moderate level of awareness and comprehension of the CEFR-aligned SBA. Reviews of past documents conducted by Zaki and Darmi (2021) showed that the implementation CEFR in classroom assessments gives several benefits to the teachers such as to track learners' learning progress, and identify learners' strengths and weaknesses in learning, so as they can plan and modify teaching methods, and take immediate follow-up actions.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Among popular issues that arose due to its implementation in many countries that have adopted it reported in studies were insufficient training on the CEFR familiarization to guide teachers adequately to take CEFR into their classroom practices, and limited knowledge and exposure to the CEFR among teachers (Ajop & Said, 2020;Alih et al, 2020;Díez-Bedmar & Byram, 2019;Foley, 2019;Kaur & Mah, 2018;Kok & Aziz, 2019;Phoolaikao & Sukying, 2021;Tosun & Glover, 2020;Uri & Aziz, 2018). In regards with the insufficient training, thus, it is a fundamental need to be addressed that most English as Second Language (ESL) teachers expressed their concerns and they claimed that they need more inservice training on CEFR (Sülü & Kır, 2014;Singh et al, 2021), and a series of training and workshop on CEFR (Khair & Shah, 2021). Countries such as Thailand, Japan, Vietnam, Malaysia, and China are no exception from having similar issues mentioned earlier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Metacognitive strategies also help learners to become more self-directed learners. This is aligned with the Primary Schools' Standards Curriculum (SCPS) that places a strong emphasis on a student-centered approach (Singh et al, 2021). Learners are better equipped to assume ownership of their own learning when they could track and assess their own progress.…”
Section: Metacognitive Strategymentioning
confidence: 99%
“…In a country that emphasises on the teaching and learning of English as a Second Language (ESL), Malaysia through the Ministry of Education (MoE) is consistently focusing on the needs of improving and enhancing the English language proficiency of students, especially at primary level. As mentioned by Singh et al (2021), this can be observed through the implementations of educational reforms to enhance the English language proficiency of primary students through modules design approach related to the four language skills namely listening, speaking, reading and writing under the Standard Curriculum for Primary Schools (SCPS) in 2011. Besides the introduction to phonics, language arts and writing, Critical and Creative Thinking Skills (CCTS) is also prioritised to promote Higher Order Thinking Skills among primary students.…”
Section: Literature Review Teaching and Learning Of English As A Seco...mentioning
confidence: 99%
See 1 more Smart Citation